Partition problems in high dimensional boxes - Bucic, Matija; Lidický, Bernard; Long, Jason; Wagner, Adam Zsolt (Journal of combinatorial theory. Series A, 2019)
Alon, Bohman, Holzman and Kleitman proved that any partition of a d-dimensional discrete box into proper sub-boxes must consist of at least 2d sub-boxes. Recently, Leader, Milićević and Tan considered the question of how many odd-sized proper boxes are needed to partition a d-dimensional box of odd size, and they asked whether the trivial construction consisting of 3d boxes is best possible. We show that approximately 2.93d boxes are enough, and consider some natural generalisations.